IDENTIFICATION OF FLOOD CHARACTERISTICS AND VULNERABILITY LEVELS IN KOTAMOBAGU CITY USING THE COMPOSITE MAPPING ANALYSIS (CMA) METHOD - Mursid, Azzahra; Mononimbar, Windy; Prijadi, Rachmat (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
<article class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:5a373193-c4fb-4a20-949a-454c9f03cae9-1" data-testid="conversation-turn-4" data-scroll-anchor="true" data-turn="assistant"> <div class="[--thread-content-max-width:40rem] thread-lg:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="dc35b7b6-ba9c-410d-85fc-c8c608d1f8e4" data-message-model-slug="gpt-5"> Kotamobagu City, as one of the strategic areas in North Sulawesi, faces major challenges related to recurring annual floods. This study aims to map flood-prone areas in Kotamobagu City using the Composite Mapping Analysis (CMA) method. The method integrates several important variables such as rainfall, slope gradient, land cover, soil texture, and distance from rivers, which are then analyzed through a Geographic Information System (GIS). The results of the study indicate that, from the total research area, there are five categories of flood vulnerability: very low, low, moderate, high, and very high. Areas with very high flood vulnerability are widely distributed across several districts, particularly in regions with a high level of urbanization and poor drainage capacity. Furthermore, the main factors causing floods in Kotamobagu are the overflowing of rivers due to heavy rainfall and uncontrolled land-use conversion in upstream areas. This research provides an accurate flood vulnerability map, which can serve as a strategic foundation for the local government in planning more effective mitigation efforts and reducing flood disaster risks in the future.